Imaging of suspected pulmonary embolism and deep venous thrombosis in obese patients - Cascio, Vincent (Br J Radiol, 2018)
Obesity is a growing problem around the world, and radiology departments frequently encounter difficulties related to large patient size. Diagnosis and management of suspected venous thromboembolism, in particular deep venous thrombosis (DVT) and pulmonary embolism (PE), are challenging even in some lean patients, and can become even more complicated in the setting of obesity. Many obstacles must be overcome to obtain imaging examinations in obese patients with suspected PE and/or DVT, and to ensure that these examinations are of sufficient quality to diagnose or exclude thromboembolic disease, or to establish an alternative diagnosis. Equipment limitations and technical issues both need to be acknowledged and addressed. Table weight limits and scanner sizes that readily accommodate obese and even morbidly obese patients are not in place at many clinical sites. There are also issues with image quality, which can be substantially compromised. We discuss current understanding of the effects of patient size on imaging in general and, more specifically, on the imaging modalities used for the diagnosis and treatment of DVT and PE. Emphasis will be placed on the technical parameters and protocol nuances, including contrast dosing, which are necessary to refine and optimize images for the diagnosis of DVT and PE in obese patients, while remaining cognizant of radiation exposure. More research is necessary to develop consistent high-level evidence regarding protocols to guide radiologists, and to help them effectively utilize emerging technology.